Leachate Characterization and Evaluation of Ground Water Quality Around Landfill Area Using the Canadian Council Ministers of the Environment Water Quality Index - Jalal, Sayran Yousif; Darwesh, Dalshad Aziz (Iraqi Journal of Science, 2023)
Municipal solid waste generation, management, and dumping are economic and ecological concerns that metropolitan areas, particularly those in developing nations, must address. This study intended to ascertain the impacts of solid waste on the quality of groundwater around trash dumps located inside and surrounding landfill sites in the city of Erbil. Samples of groundwater, as well as two samples of leachate, were collected from eight wells situated near landfills during the dry and rainy seasons of August 2021 and February 2022. Several physico-chemical parameters, including pH, EC, NO2, NO3, alkalinity, HCO3, Na, Ca, Mg, Cl, SAR, total hardness, and heavy metals, were evaluated in the samples. During fieldwork, water quality index (z) measurements for summer and winter were combined with longitude (x) and latitude (y) information gathered by GPS. Using the inverse distance weighting approach, integrated xyz data was interpolated in ArcMap GIS software to measure the groundwater quality of the research region. According the CCME Water Quality Index, wells 4 and 8 had WQIs ranging from fair to marginal in both the winter and summer seasons (WQI). According to the data, cadmium contents in summertime were much greater (0.430–2.066 mg. l-) than the WHO standard (0.003 mg. l-1), deeming them unfit for human use. And that the high lead level in the summer (0.843-2.600 mg. l-1) is caused by too many Pb batteries being thrown away.